2016
DOI: 10.1164/rccm.201512-2316pp
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Pulmonary Fibrosis: Novel Concepts of Proton Pump Inhibitors as Antifibrotic Drugs

Abstract: The prevalence of abnormal acid gastroesophageal reflux (GER) is higher in patients with idiopathic pulmonary fibrosis (IPF) than in matched control subjects. Several studies demonstrated that more than one-third of patients with IPF have abnormal esophageal acid exposures. In addition, many of these studies indicate that the majority of patients with IPF have silent reflux with no symptoms of GER. Findings of abnormal reflux persist in a large proportion of patients with IPF placed on antacid therapy such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 62 publications
3
70
1
2
Order By: Relevance
“…Evidence obtained from asymmetrical fibrosis further support the contribution of GOR to disease progression [10]. These data support the hypothesis that treating GOR may influence IPF behaviour, and many mechanisms have been proposed to explain a potential benefit of GOR treatment in IPF [11].…”
supporting
confidence: 62%
“…Evidence obtained from asymmetrical fibrosis further support the contribution of GOR to disease progression [10]. These data support the hypothesis that treating GOR may influence IPF behaviour, and many mechanisms have been proposed to explain a potential benefit of GOR treatment in IPF [11].…”
supporting
confidence: 62%
“…One prospective observational study showed reduced disease progression regarding FVC and exacerbations [100] , while a new post hoc evaluation of clinical studies on IPF shows increased numbers of overall and pulmonary infections in advanced IPF patients treated with antacids compared to those not treated with antacids [101] . Furthermore, patients with antacid treatment at baseline receiving nintedanib seemed to do worse than those without antacid treatment [99] . Promising surgical interventions to inhibit acid as well as anti-acid reflux with Nissen fundoplication in IPF are currently studied in an ongoing clinical trial (WRAP-IPF) [99] .…”
Section: Should Gastroesophageal Reflux Be Treated In Ipf?mentioning
confidence: 94%
“…Nevertheless, gastroesophageal reflux is considerably prevalent in patients with IPF. Anti-reflux treatment, however, has been controversially discussed [99] . One prospective observational study showed reduced disease progression regarding FVC and exacerbations [100] , while a new post hoc evaluation of clinical studies on IPF shows increased numbers of overall and pulmonary infections in advanced IPF patients treated with antacids compared to those not treated with antacids [101] .…”
Section: Should Gastroesophageal Reflux Be Treated In Ipf?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are significant concerns regarding the design of that study, and the results must be interpreted with caution [11]. While recent perspectives on the topic discuss the potential and prospects of the antifibrotic properties of proton pump inhibitors (PPIs), several questions regarding the use of PPIs and antiacid treatment need to be answered [11,12]. In a recent retrospective study, the safety of laparoscopic antireflux surgery in patients with IPF demonstrating abnormal acid gastro-oesophageal reflux (GOR), and a trend to slow the rate of decline in FVC over a year were demonstrated [13].…”
Section: Current Landscape Of Pharmacotherapy For Patients With Ipfmentioning
confidence: 99%